Just as they expected: How parents' expectations about their unborn child's characteristics provide a context for early transactions between parenting and child temperament - Van den Akker, Alithe L.; Majdandzic, Mirjana; de Vente, Wieke; Asscher, Jessica J.; Bögels, Susan (Frontiers in Psychology, 2022)
Prenatal expectations about what children will be like after birth may provide a context for how parents perceive their infant's actual temperament. We examined how these expectations and perceptions are associated and together predict early parenting behavior, with parenting behavior in turn predicting changes in temperament. Reports of 125 families (N = 122 fathers; N = 123 mothers; sample 1) about their expectations of their unborn child's temperament (negative affectivity, surgency, regulation, T1), their infant's temperament at 4 and 12 months post-partum (T2 and T3), and their hostile, responsive, warm, and overprotective parenting (T2) were included. We also included data from an independent sample of 168 mothers (sample 2), with the same measures, except that mothers reported on Big Five personality traits at T1. Results indicated that in both samples, parents' expectations were positively associated with perceptions of infant temperament. Prenatal expectations and newborn temperament independently predicted parenting behavior, and maternal and paternal parenting in turn predicted infant temperament at T3, controlling for infant temperament at T2. Although overall findings indicated associations between (expectations of) a more difficult temperament and more negative/less positive parenting, significant combinations of specific traits and parenting behaviors were sample-specific—indicating that more research is necessary to draw a conclusion about specific links. Both maternal and paternal expectations about their unborn child's temperament appear to carry over into the postpartum reality and provide a context for shaping early interactions between caregivers and their children, which may further shape the developing temperament of the child.